Transcendentalist Women in Conversation: Margaret Fuller, Sophia Ripley, and “Woman” - Alice de Galzain (Transatlantica)
This essay focuses on Sophia Ripley’s 1841 article “Woman,” which was published in the Dial two years before Margaret Fuller’s “The Great Lawsuit. Man Versus Men. Woman Versus Women” appeared in the same publication. Originally written as homework for one of Fuller’s Boston Conversations (1839–1844), Ripley’s plea in favor of women’s right to education perfectly epitomizes the polyphonic nature of feminist social advances in antebellum America. Inspired by Fuller’s feminist reinterpretation of William Ellery Channing’s concept of “self-culture,” viewing education as a means to improve woman’s condition, Ripley’s text debunks the concept of “separate spheres” and urges readers to consider women as intellectual beings rather than through the prism of the idealized, unrealistic “muse.” Inscribing Ripley’s article as part of the feminist stride of the Transcendental movement, I will illustrate the similarities between Ripley’s argument, Fuller’s, and that of other women Transcendentalists, while also confronting it with what Ralph Waldo Emerson wrote on the subject.